1998
DOI: 10.1093/ps/77.8.1146
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasmas in the etiology of multifactorial respiratory disease

Abstract: The avian mycoplasmas pathogenic for commercial poultry, Mycoplasma gallisepticum and Mycoplasma synoviae in chickens and turkeys, and Mycoplasma meleagridis and Mycoplasma iowae in turkeys are egg-transmitted infections and exhibit wide variations in clinical manifestations. Mycoplasma gallisepticum strains vary widely in virulence, tissue tropism, and antigenic makeup and have the ability to alter the expression of major surface antigenic proteins. Although less well studied, strains of M. synoviae, M. melea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 41 publications
5
89
0
3
Order By: Relevance
“…Infection can produce disease that ranges from subclinical to severe, and clinical outcome can be influenced by co-infection with other agents [4,5,6,7,8]. The majority of prior studies have focused on cytadherence and/or hemadsorption as pathogenic mechanisms of M. synoviae, with particular attention to antigenically-variable hemagglutinins, although the molecular basis of M. synoviae pathogenicity is still not well-understood [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Infection can produce disease that ranges from subclinical to severe, and clinical outcome can be influenced by co-infection with other agents [4,5,6,7,8]. The majority of prior studies have focused on cytadherence and/or hemadsorption as pathogenic mechanisms of M. synoviae, with particular attention to antigenically-variable hemagglutinins, although the molecular basis of M. synoviae pathogenicity is still not well-understood [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations vary by strain, and some appear to have a greater tropism for synovial membanes or the respiratory tract than others (21). Disease is often complicated by co-infection with other pathogens, most notably Newcastle disease virus, infectious bronchitis virus, infectious bursal disease virus, Escherichia coli, Mycoplasma gallisepticum and Mycoplasma meleagridis (11,20,32,37,38). The molecular basis of M. synoviae virulence is not well-understood.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, penicillin G-exposed Chlamydiae can reenter the normal developmental cycle upon drug removal ( There might be a pathogenic interaction between C. psittaci and other viral and/or bacterial respiratory pathogens. Interactions between respiratory pathogens have already been demonstrated for M. gallisepticum and NDV in experimentally infected chickens (reviewed by Kleven, 1998) The presence of C. psittaci in empty barns and in 1-day-old broilers remains intriguing. Vertical transmission occurs in chickens (Wittenbrink et al, 1993) and bio-aerosol monitoring during hatching revealed increasing numbers of C. psittaci (Dickx & Vanrompay, 2011).…”
Section: Discussionmentioning
confidence: 99%